Detailed Study of the Reaction Mechanisms of 86Kr + 64Ni at 15 MeV/nucleon - Fasoula, Olga; G. A. Souliotis; S. Koulouris; M. Veselsky; S. J. Yenello; A. Bonasera (HNPS Advances in Nuclear Physics, 2024)
We present a detailed study of momentum distributions of projectile fragments from the reaction 86Kr + 64Ni at 15 MeV/nucleon. The experimental data were obtained in previous work with the MARS separator at the Cyclotron Institute of Texas A&M University. Detailed calculations and the momentum distributions of ejectiles are presented and compared with the experimental data. The DIT and CoMD models are used for the dynamical part of the reaction and GEMINI is used for the de-excitation of the primary fragments. Our focus is on channels corresponding to the production of neutron rich nuclei. Both DIT and CoMD show promising results in the description of the experimental data, but further developments may be necessary. Through the systematic study of the momentum distributions, we try to elucidate the reaction mechanisms that dominate the production of neutron rich nuclei in the Fermi energy region.